A competitive luminol chemiluminescence immunosensor based on a microfluidic chip for the determination of ractopamine. Issue 2 (7th June 2016) - Wang, Sai; Chen, Qilong; Wei, Xiao; Wu, Jian; Wang, Chunyan; Liu, Jiahui; Zhang, Liya; Dong, Yiyang
Abstract : Herein, a competitive luminol chemiluminescence immunosensor based on a microfluidic chip was developed to detect ractopamine (RCT) both in phosphate buffer and swine urine samples. The immunosensor can provide a liner range of 0.5–40 ng/mL and a high sensitivity with a limit of detection of 0.97 ng/mL for RCT detection in swine urine. Good rates of recovery in negative swine urine samples were achieved over the RCT concentration ranging from 0.5 to 40 ng/mL. The proposed method offered a promising analytical scheme for the on‐site determination of RCT.